THE MIDDLE CARADOC FACIES AND FAUNAL TURNOVER IN THE LATE ORDOVICIAN BALTOSCANDIAN PALAEOBASIN - Ainsaar L.; Meidla T.; Martma T. (My University, 2004)
A Late Ordovician episode of remarkable biotic, climatic, sea level and facies changes, named here as the Middle Caradoc Facies and Faunal Turnover, took place in the Baltoscandian area. This paper presents an integrated overview of these changes in the critical middle Caradoc interval. Data are given on carbonate rock composition, distribution and grain-size composition of the siliciclastic material and the carbon isotopic composition of whole-rock carbonates in cores of Estonia and Sweden.The Middle Caradoc Facies and Faunal Turnover can be described as a succession of related environmental changes. The turnover began with a positive excursion in carbonate δ13C and continued with sea level changes that led to a sedimentary hiatus on the shelf and a change from carbonate-dominated to siliciclastic-dominated sedimentation in the basin. The turnover ended with an extinction event and associated microfaunal crisis.The middle Caradoc turnover in Baltoscandia is comparable to a similar succession of changes in North America. The turnover affected two palaeocontinents, and reflects a widespread, possibly global environmental change. Onset of glaciation on Gondwana and/or increased orogenic activity might have initiated the changes in ocean circulation and led to the initial carbon isotope excursion. The following sea level rise and faunal changes affected several different continents.
Keywords: Late Ordovician; Stable carbon isotopes; Faunal change; Sedimentology; Baltica; Estonia; Sweden; Paleozoic::Ordovician; Палеозой::Ордовикская